Down home : Jewish life in North Carolina - Rogoff, Leonard (Published in association with the Jewish Heritage Foundation of North Carolina by the University of North Carolina Press, 2010)
A sweeping chronicle of Jewish life in the Tar Heel State from colonial times to the present, this beautifully illustrated volume incorporates oral histories, original historical documents, and profiles of fascinating individuals. More than 125 historic and contemporary photographs complement Rogoff's engaging epic, providing a visual panorama of Jewish social, cultural, economic, and religious life in North Carolina.